Penerapan Digitalisasi Transaksi Melalui Mesin TCR Untuk Nasabah BNI Kantor Cabang Jakarta Kota - Risda Dewi Amanda; Edy Safni Rosa; Wadudi Wibowo; Wimpi Srihandoko (Jurnal Aplikasi Bisnis Kesatuan, 2025)
PT Bank Negara Indonesia (Persero), Tbk. BNI was designated "Bank Negara Indonesia 1946," and its status changed to a State-Owned Commercial Bank. PT Bank BNI is a general banking company. Many in-person transactions at PT Bank BNI result in long queues, leading to customer dissatisfaction with the fast service process. TCR machines are one of the money counting machines provided by the head office as an aid to tellers and to help customers conduct more digital transactions. TCR machines significantly assist customers in depositing and withdrawing money. Currently, TCR machines are increasingly found at BNI branch offices and outlets. To calculate the number of transactions using TCR machines, the author used the difference in usage from the beginning to the last three months, observing the average amount of money deposited into the TCR machine vault. To determine how many customers have made the shift to digital, the author used a quarterly data collection method to determine the increase in daily customer transactions. The results of this calculation will then be used as a value for PT. BNI Bank is improving its facilities and infrastructure so customers can conduct more transactions themselves without having to queue at the teller. Keywords: Transaction Digitalization, TCR (Teller Cash Recycler) Machines